Soil viruses drive carbon turnover during subtropical secondary forest succession - Chen, Xingyi; Yu, Danting; Yan, Yuting; Yuan, Chengyu; He, Jizheng (Frontiers in Microbiology, 2025)
IntroductionSoil viruses are increasingly recognized as key regulators of microbial ecology and ecosystem function, yet their roles in forest ecosystems, particularly during natural secondary succession, remain largely unexplored.MethodsWe examined soil viral communities across five successional stages of secondary forests to investigate their taxonomic dynamics and functional potential. Using high-throughput viral metagenomics, we characterized viral community structure, abundance, and auxiliary metabolic gene content.ResultsOur results demonstrate that soil viral abundance and community composition shift significantly with forest stand age. Viral richness increased during succession, with compositional transitions observed across stages; however, tailed bacteriophages consistently dominated. Structural equation modeling and linear mixed-effects analysis identified soil pH and bacterial diversity as primary environmental determinants of viral diversity. Functionally, soil viruses harbored auxiliary metabolic genes related to carbohydrate metabolism, indicating their potential involvement in modulating host metabolic processes. Successional trends in viral functional profiles revealed a transition from carbon assimilation to carbon release pathways, suggesting viral mediation of carbon turnover. Notably, the enrichment of glycoside hydrolase and glycosyl transferase genes across forest ages implies a role for viruses in shaping microbial carbon processing capacities through carbohydrate-active enzyme contributions.DiscussionThese findings provide novel evidence that soil viruses actively participate in ecosystem succession by influencing microbial functional potential and biogeochemical cycling. This study underscores the ecological importance of soil viral communities in regulating carbon dynamics during secondary forest development.